The molecular organography of plants - Cronk, Quentin C. B. (Oxford : Oxford University Press, 2009)
The history of plant evolution has been one of increasing complexity. The field of 'evo-devo' (evolution of development) seeks to explain this diversity by examining the evolution of the molecular and developmental processes responsible for plant form. This book surveys the structural complexity of plant form within this new framework.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Botany -- Organography; Plant molecular biology